Estimation of sulphur dioxide emission from consumption of premium motor spirit and automotive gas oil in Nigeria - Okedere, O.B.; Ajala, Olawale E.; Sonibare, Jacob; Adesina, Olusola (Cogent Environmental Science, 2023)
Cogent Environmental Science,P.1-17